Formulation Strategies in Psoriasis: Journey from Traditional Preparations to Advanced Drug Delivery Systems - Obaid, Shahad; Qasim, Yasir (Journal of Pharmacology and Drug Development, 2026)
ABSTRACT Psoriasis (PSO) is an immune-mediated dermatological disorder marked by thick, erythematous, scaly plaques resulting from rapid, excessive cellular growth. Anti-inflammatory agents, immunosuppressant’s, and additional pharmaceuticals serve as the principal therapeutic strategy for psoriasis to alleviate symptoms, diminish inflammation, and inhibit the proliferation and division of epidermal cells. Nevertheless, these drugs generally include disadvantages that impose significant physiological and pathological burdens on patients, including inadequate targeting, brief half-lives, limited absorption rates, and severe toxic side effects. Researchers have recently concentrated significant effort on employing delivery systems for the topical administration of drugs to affected psoriatic skin regions. These systems increase pharmacological efficacy, stability, and penetration. More therapeutic concepts for the treatment of PSO are made possible by the ongoing development of numerous multifunctional topical delivery technologies. This publication reviews various delivery strategies, including hydrogels, nanoparticles, microneedles, micelles, dendrimers, liposomes, nanoemulsions, and vesicles, for topical therapy of PSO and delineates their current developmental status in clinical treatment. It is expected to facilitate the progression of PSO treatment methodologies and provide a benchmark for the development of novel topical delivery systems.